2019
DOI: 10.1111/sed.12573
|View full text |Cite
|
Sign up to set email alerts
|

Neogene palaeoceanographic changes recorded in a carbonate contourite drift (Santaren Channel, Bahamas)

Abstract: The Santaren Drift between the Great Bahama Bank and Cay Sal Bank (Bahamas) is closely linked to the development of the Gulf Stream and its shape and geometry record the local to global oceanographic, climatic and tectonic events since the Miocene. High-resolution multichannel seismic data from the Santaren Channel allow detailed insight into the growth phases of the contourite drift, and by using the stratigraphic information from Ocean Drilling Program Site 1006 to infer its sedimentation rates. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 81 publications
(138 reference statements)
3
23
0
Order By: Relevance
“…). The drift body is lined by current moats towards the slopes of GBB and CSB (Anselmetti et al ., ; Lüdmann et al ., ; Wunsch et al ., ; Paulat et al ., ). These moats form shallow sea floor depressions (up to 22 m deep) of varying width.…”
Section: Study Areamentioning
confidence: 97%
See 1 more Smart Citation
“…). The drift body is lined by current moats towards the slopes of GBB and CSB (Anselmetti et al ., ; Lüdmann et al ., ; Wunsch et al ., ; Paulat et al ., ). These moats form shallow sea floor depressions (up to 22 m deep) of varying width.…”
Section: Study Areamentioning
confidence: 97%
“…Here, the material mixes with carbonate from pelagic sources forming periplatform ooze redistributed by oceanic currents. As a result, large carbonate drifts develop at the foot of the platform slopes and at the bottom of the marine straits that intersect the Bahamian archipelago since the Miocene (Bergman, ; Betzler et al ., ; Lüdmann et al ., ; Paulat et al ., ). The sediment of these drifts, albeit dominated by carbonate and subordinate biogenic silica, contains a terrigenous fraction, mainly clay minerals and quartz.…”
Section: Introductionmentioning
confidence: 97%
“…Up to now, carbonate drifts have not been as broadly investigated as their siliciclastic equivalents (Stow et al ., ; Viana & Rebesco, ; Rebesco & Camerlenghi, ; Rebesco et al ., ). Several studies, however, document their importance in the development of tropical carbonate platform edifices (Mullins et al ., ; Anselmetti et al ., ; Isern et al ., ; Betzler et al ., , , ; Eberli et al ., ; Lüdmann et al ., , ; Mulder et al ., ; Paulat et al ., ). Studies on the ichnology of siliciclastic drifts have demonstrated that such deposits are characterized by a high degree of bioturbation (Stow et al ., , ; Wetzel et al ., ; Rebesco et al ., ; Rodríguez‐Tovar & Hernández‐Molina, ).…”
Section: Introductionmentioning
confidence: 97%
“…The Bahamas archipelago is a carbonate province consisting of several isolated platforms situated at the southern end of the eastern continental margin of the United States. In the Santaren Channel, at a water depth of ca 600 to 700 m and ca 30 km from the western platform edge of the Great Bahama Bank, there is a continuous drift sequence which is Neogene to present day in age, that interfingers with prograding carbonate‐bank deposits of the Bahamas (Eberli et al ., ; Kroon et al ., ; Anselmetti et al ., ; Bergman et al ., ; Paulat et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The external morphology and internal architecture of these deposits have been studied widely leading to a synoptic classification based predominately on siliciclastic drifts (Stow et al ., ,b; Hernández‐Molina et al ., ; Rebesco et al ., ). In contrast, the knowledge about carbonate drifts is limited and restricted to deposits either at the flanks of the banks as periplatform drifts (Mullins & Neumann, ; Mullins et al ., ; Betzler et al ., ; Chabaud et al ., ), in seaways separating carbonate banks as detached drifts (Anselmetti et al ., ; Bergman, ; Lüdmann et al ., ; Paulat et al ., ), or at the downcurrent end of shallow passages dissecting carbonate banks as delta drifts (Lüdmann et al ., , ).…”
Section: Introductionmentioning
confidence: 99%